2018
DOI: 10.1186/s13046-018-0831-2
|View full text |Cite
|
Sign up to set email alerts
|

LINC01287/miR-298/STAT3 feedback loop regulates growth and the epithelial-to-mesenchymal transition phenotype in hepatocellular carcinoma cells

Abstract: BackgroundThe long non-coding RNAs (lncRNAs) have participated in the promotion of hepatocellular carcinoma (HCC) initiation and progression. Nevertheless, the biological role and underlying mechanism of LINC01287 in HCC has never been reported.MethodsThe TGCA database was used to explore the abnormal expression of lncRNAs in HCC. Real-time PCR and in situ hybridization assays were used to examine the expression of LINC01287 in HCC tissues. The clinicopathological characteristics of HCC patients in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…For example, lncRNA CDKN2BAS accelerates metastasis in HCC by sponging miR-153-5p and targeting ARHGAP18 [19]. LINC01287/miR-298/STAT3 feedback loop modulates cell growth and the epithelial-to-mesenchymal transition in HCC [20]. LINC01433 facilitates the development of HCC by regulating the miR-1301/STAT3 axis [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA CDKN2BAS accelerates metastasis in HCC by sponging miR-153-5p and targeting ARHGAP18 [19]. LINC01287/miR-298/STAT3 feedback loop modulates cell growth and the epithelial-to-mesenchymal transition in HCC [20]. LINC01433 facilitates the development of HCC by regulating the miR-1301/STAT3 axis [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to some other studies (7), miR-15a can affect the proliferation and apoptosis of thyroid cancer cells by regulating AKT. Among those miRNAs, miR-298, located on human chromosome 20q13.32, is related to the proliferation and invasion of tumor cells according to recent studies (8). For example, a study found that miR-298 could affect the proliferation and invasion of ovarian cancer cells by regulating the expression of EZH2 (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that lncRNAs are involved in the EMT phenotype. For example, LINC01287 promotes EMT progression to enhance HCC cell invasion via the LINC01287/miR-298/STAT3 feedback loop [32]. LncRNA UCA1 promotes EMT by enhancing Wnt/β-catenin signalling in breast cancer cells [33].…”
Section: Discussionmentioning
confidence: 99%